Aforização no hipergênero youtube: vídeos ligados ao Escola sem partido - Marinho, Adriano Souza (2024)
From the 2013 protests, the far right gained strength in Brazil, culminating in the impeachment of Dilma Rousseff in 2016 and the election of Jair Bolsonaro in 2018. In this context, the Escola Sem Partido Movement (MESP) emerged as an ideological front of the new right, seeking to restrict and monitor pedagogical practices in schools. One of the mechanisms used by MESP to execute this agenda was the encouragement of recording classes and denouncing teachers who, according to its defenders, were inserting political-partisan content into their lessons. With this in mind, this study aims to analyze the process of aphorization of teachers' classes in YouTube videos related to MESP, investigating the types of aphorization that occur and identifying the modifications that take place in relation to the source texts, caused by the linguistic, visual, and auditory resources used in the scene of aphorization. Additionally, it discusses the changes that teachers' speeches undergo when they become aphorizers in such videos. The theoretical basis of the study is composed of concepts from Discourse Analysis, with emphasis on Dominique Maingueneau's approach (2006, 2010, 2013, 2014, 2015) on aphorization. It also incorporates theories by Paveau, who explores the main forms and discursive practices found on digital platforms; Oliveira (2022), who examines the discursive formula "Escola Sem Partido," investigating how discourses contribute to shaping perceptions about the role of the school, teachers, and pedagogical content; Burgess & Jean (2009), who explore how YouTube has transformed communication and media consumption, analyzing its social, cultural, and economic impacts; and Araújo (2002), who investigates the main characteristics and practices involved in the creation of two common types of subtitles in Brazil: closed captions and open captions.